2013
DOI: 10.1517/17460441.2013.798296
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the development of hybrid anticancer drugs

Abstract: The current development in the field describes strategies that have never been used before for the design of hybrid anticancer drugs. The information currently available and described in this section allows us to identify the main parameters required to design such molecules. It also provides a clear view of the future directions that must be explored for the successful development and discovery of useful hybrid anticancer drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(152 citation statements)
references
References 67 publications
1
145
0
6
Order By: Relevance
“…72,79,80 More so, as an emerging area in drug development, the hybrid concept is beset with initial challenges that are not remarkably unexpected of any new field of endeavor. For instance, the physicochemical properties of most hybrid drugs, owing to their large molecular weight, are highly unpredictable and they tend to deviate from the generally acknowledged drug-like properties of medicinal agents.…”
Section: Limitationsmentioning
confidence: 99%
“…72,79,80 More so, as an emerging area in drug development, the hybrid concept is beset with initial challenges that are not remarkably unexpected of any new field of endeavor. For instance, the physicochemical properties of most hybrid drugs, owing to their large molecular weight, are highly unpredictable and they tend to deviate from the generally acknowledged drug-like properties of medicinal agents.…”
Section: Limitationsmentioning
confidence: 99%
“…A number of molecules of this type have been described in previous reviews [8,9]. Since DNA topoisomerases I and II (topo I and II) are recognized as the primary targets of well-established antitumour drugs, hybrid compounds containing topo I/topo II inhibitors have been explored.…”
Section: Hybrid Compounds Incorporating Cytotoxic Agentsmentioning
confidence: 99%
“…Class I: chimeric/hybrid pharmacophore designs Hybrid anticancer agents are of great therapeutic interest as they can potentially overcome most of the pharmacokinetic drawbacks encountered when using conventional anticancer drugs (Fortin and Berube, 2013). A chemical entity constituting two structural domains, depicting dissimilar action as an outcome of acting through different modes of actions are called as hybrid drugs, thus indicating that a hybrid molecule acts as two distinct pharmacophores.…”
Section: Classificationmentioning
confidence: 99%
“…A chemical entity constituting two structural domains, depicting dissimilar action as an outcome of acting through different modes of actions are called as hybrid drugs, thus indicating that a hybrid molecule acts as two distinct pharmacophores. Hybrid anticancer drugs are designed on the basis of combining a haptophoric moiety or merging two or more drugs (Fortin and Berube, 2013;Hulsman et al, 2007). Ko et al recently revealed and synthesized the hybrid histone deacetylase (HDAC) inhibitor and c-Src inhibitor (non-receptor tyrosine kinase) (Ko et al, 2013).…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation